Atopy and wheeze in children according to parental atopy and family size. Issue 3 (March 1981) - Davis, J B; Bulpitt, C J
Abstract : The relationship between atopy and wheeze was examined in children, together with the possible influence on these conditions of parental atopy and family size. Children with a repeated history of wheezing were selected from an urban general practice population. The children, their first degree relatives, and a control group were examined for atopic status, atopy being defined as more than one positive immediate skin prick test response. The prevalence of wheeze in boys was 15.5%, in girls 7.6%, and of atopy in boys 19.7% and in girls 8.1%. Of 110 atopic children 70% had no atopic parent, 27% had one atopic parent, and in 3% both parents were atopic. The presence of parental atopy was associated with an increased prevalence of wheeze in boys but not in girls, 12.0% of boys having a history of wheezing if neither parent was atopic and 27.5% if either or both parents were atopic (p less than 0.05). The presence of parental atopy was associated with an increased prevalence of atopy in girls but not in boys, 6.1% of girls having atopy if neither parent was atopic and 18.9% if either or both parents were atopic (p less than 0.01). There was a strong association between atopy and wheeze for both sexes and no statistically significant difference in the prevalence of atopy or wheeze in children whether they were from two, three, or four child families.